An enhanced safrole sensing performance of a olyacrylonitrile nanofiber-based-QCM sensor by overlaying with chitosan - Rianjanu, Aditya; Triyana, Kuwat; Novalia Nurbaiti,; Siti Astuti Hasanah,; Kusumaatmaja, Ahmad; Roto, Roto (Penerbit Universiti Kebangsaan Malaysia, 2019)
We report on a method to enhance the sensing performance of polyacrylonitrile (PAN) nanofiber-based QCM sensor overlaid with chitosan. The PAN nanofibers were deposited on the QCM sensing surface by electrospinning technique followed by overlay with chitosan by a drop-casting method. The Fourier transform infrared (FTIR) spectra confirm that chitosan covers the PAN nanofibers. The SEM images show the average diameter of the produced PAN nanofibers was 236 nm, and it increased to 283 nm after overlay with chitosan. The modified QCM sensor has the sensitivity of 18.7 Hz mg-1 L, which is better than that of PAN nanofiber alone of 4.5 Hz mg-1 L. It is an increase nearly 5 times. The analytical parameters of the limit of detection (LOD), sensitivity, a time constant, and stability improved after the PAN nanofiber sensor was overlaid with chitosan. The amine groups present in chitosan interact effectively with safrole, thus increase the sensing response. The proposed device is robust, inexpensive, and convenient for detecting safrole, and can be used as an alternative to those of classical instrumental methods for the analysis of safrole as a drug precursor.